Brucella Shunt Infection Complicated by Peritonitis: Case Report and Review of the Literature - Rawan Al-Qarhi; Mona Al-Dabbagh (MDPI AG, 2021)
Brucellosis is an endemic zoonotic disease in the Mediterranean basin and Middle East. The disease remains a diagnostic challenge due to an increasing trend of ambiguous and non-specific manifestations. We report a rare case of a 9-year-old boy who had a left frontotemporal arachnoid cyst with cystoperitoneal shunt who presented with fever for 2 weeks with gastrointestinal symptoms. He had no neurological manifestations. Diagnosis of Brucella shunt infection complicated with a peritoneal collection was established by isolation of the organism from cerebrospinal fluid (CSF) culture. Successful treatment was accomplished by shunt replacement and intravenous antibiotics followed by step-down oral therapy for an 18-month duration based on serological and radiological responses with no sequelae. We also reviewed the reported cases of CSF shunt infection in the literature for further guidance. Brucella shunt infection may be difficult to diagnose due to the diversity of signs and symptoms and the low yield on culture. Brucellosis should be always kept in mind in the differential diagnosis of patients living in endemic area with fever and non-specific symptoms. Diagnosis depends on a high index of suspicion. In addition to drug therapy, device replacement is advised to prevent treatment failure.